PENGARUH NISBAH BAGI HASIL TERHADAP PENGHIMPUNAN DANA BANK SYARIAH (STUDI KASUS PADA PRODUK TABUNGAN DI BPR SYARIAH KOTA BEKASI) - Fitriah, Eliza; Buchori, Nur S. (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2011)
This study aims to determine and analyze the effect of profit sharing ratio of fund raising as well as to determine the effect of profit sharing ratio of Islamic banks mobilize funds Bekasi. The method used in this research is descriptive quantitative analysis. From this study it can be concluded that based on the F test showed that the ratio for the outcome variable is jointly significant effect on the variables of Islamic banks mobilize funds. Based on the results of Pearson Product Moment correlation test that the value obtained for 0.565 means there is a fairly strong relationship between variables and variable profit sharing ratio of Islamic banks mobilize funds. The test results obtained regression equation Y: 2229 X +0.435. The equation shows that there is influence between the profit sharing ratio of the fund raising Financing Bank Rakyat Syariah Bekasi Based on the test R Square of 0.619 indicates that the fund-raising (Y) of 61.9% is affected by the profit sharing ratio (X). While the rest of 38.1%caused by other variables.